Patient‐derived xenografts of gastrointestinal cancers are susceptible to rapid and delayed B‐lymphoproliferation. Issue 6 (15th March 2017) - Dieter, Sebastian M.; Giessler, Klara M.; Kriegsmann, Mark; Dubash, Taronish D.; Möhrmann, Lino; Schulz, Erik R.; Siegl, Christine; Weber, Sarah; Strakerjahn, Hendrik; Oberlack, Ava; Heger, Ulrike; Gao, Jianpeng; et al.
Abstract : Patient‐derived cancer xenografts (PDX) are widely used to identify and evaluate novel therapeutic targets, and to test therapeutic approaches in preclinical mouse avatar trials. Despite their widespread use, potential caveats of PDX models remain considerably underappreciated. Here, we demonstrate that EBV‐associated B‐lymphoproliferations frequently develop following xenotransplantation of human colorectal and pancreatic carcinomas in highly immunodeficient NOD.Cg‐ Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice (18/47 and 4/37 mice, respectively), and in derived cell cultures in vitro . Strikingly, even PDX with carcinoma histology can host scarce EBV‐infected B‐lymphocytes that can fully overgrow carcinoma cells during serial passaging in vitro and in vivo . As serial xenografting is crucial to expand primary tumor tissue for biobanks and cohorts for preclinical mouse avatar trials, the emerging dominance of B‐lymphoproliferations in serial PDX represents a serious confounding factor in these models. Consequently, repeated phenotypic assessments of serial PDX are mandatory at each expansion step to verify "bona fide" carcinoma xenografts. Abstract : What's new? Despite the routine and extensive use of patient‐derived cancer xenografts (PDX) in preclinical cancer research, no universal guidelines for quality testing are available. This study however demonstrates that Epstein‐Barr virus‐associated B‐lymphoproliferations frequently develop following xenotransplantation of colorectal and pancreatic cancer tissue in highly immunodeficient mice. Even minor numbers of residual EBV‐infected B‐lymphocytes present in the initial PDX can fully overgrow epithelial cancer cells during serial xenotransplantation. In addition, patient‐derived B‐lymphocytes can proliferate in culture conditions optimized for primary epithelial cancer cells. B‐lymphoproliferations represent a serious confounding factor, making repeated phenotypic assessments mandatory to verify "bona fide" carcinoma xenografts.